2019
DOI: 10.3847/1538-4357/ab30c7
|View full text |Cite
|
Sign up to set email alerts
|

The Time-resolved Spectra of Photospheric Emission from a Structured Jet for Gamma-Ray Bursts

Abstract: The quasi-thermal components found in many Fermi gamma-ray bursts (GRBs) imply that the photosphere emission indeed contributes to the prompt emission of many GRBs. But whether the observed spectra empirically fitted by the Band function or cutoff power law, especially the spectral and peak energy (E p ) evolutions can be explained by the photosphere emission model alone needs further discussion. In this work, we investigate in detail the time-resolved spectra and E p evolutions of photospheric emission from a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 113 publications
(163 reference statements)
3
57
0
Order By: Relevance
“…The photosphere models (Rees & Mészáros 2005;Pe'er et al 2006;Giannios 2008;Pe'er 2008;Beloborodov 2009Beloborodov , 2011Lazzati & Begelman 2009;Ioka 2010;Ryde et al 2011;Toma et al 2011;Aksenov et al 2013;Bégué et al 2013;Lundman et al 2013;Ruffini et al 2013Ruffini et al , 2014Deng & Zhang 2014;Meng et al 2018) invoke an even smaller emission radius than the small-radii internal shock model, which interprets the broad pulse as observed in GRB 131231A as a manifestation of the history of central engine activity. Since usually the luminosity is positively correlated to the temperature, the photosphere model usually predicts an E p -flux-tracking behavior (Deng & Zhang 2014), even though in certain structured jet geometry, a reversed (hard-to-soft evolution) pattern may be also produced (Meng et al 2019).…”
Section: Photosphere Modelsmentioning
confidence: 99%
“…The photosphere models (Rees & Mészáros 2005;Pe'er et al 2006;Giannios 2008;Pe'er 2008;Beloborodov 2009Beloborodov , 2011Lazzati & Begelman 2009;Ioka 2010;Ryde et al 2011;Toma et al 2011;Aksenov et al 2013;Bégué et al 2013;Lundman et al 2013;Ruffini et al 2013Ruffini et al , 2014Deng & Zhang 2014;Meng et al 2018) invoke an even smaller emission radius than the small-radii internal shock model, which interprets the broad pulse as observed in GRB 131231A as a manifestation of the history of central engine activity. Since usually the luminosity is positively correlated to the temperature, the photosphere model usually predicts an E p -flux-tracking behavior (Deng & Zhang 2014), even though in certain structured jet geometry, a reversed (hard-to-soft evolution) pattern may be also produced (Meng et al 2019).…”
Section: Photosphere Modelsmentioning
confidence: 99%
“…The best-fit low-energy photon index, α, evolves rapidly and tracks the flux level. Moreover, α systematically exceeds the synchrotron "death line" (Preece et al 1998) defined by α = −2/3 and reaches the highest value of ∼ −0.2 in several slices, which indicates that the spectra are thermal-like (Meng et al 2019).…”
Section: Spectral Analysismentioning
confidence: 92%
“…The radiation mechanism that powers the prompt emission of gamma-ray bursts (GRBs) remains controversial. The leading two models, namely the photospheric emission of the relativistic fireball not far from the central engine (Pe'er 2008;Zhang & Yan 2011;Geng et al 2018;Hou et al 2018;Meng et al 2018Meng et al , 2019Zhang et al 2018a) and the synchrotron emission of the Poynting flux of a magnetic outflow generated at a large radius (Zhang & Pe'er 2009;Zhang & Yan 2011;Zhang et al 2016Zhang et al , 2018a, are both successful in reproducing some observed spectra on a burst-by-burst basis. The superposition of the thermal and the non-thermal components in some GRBs (Guiriec et al 2011;Gao & Zhang 2015) further complicates the diversity and points towards a "hybrid" model.…”
Section: Introductionmentioning
confidence: 99%
“…Photospheric emission was successfully identified in several bursts observed by BATSE (Ryde 2004(Ryde , 2005Ryde & Pe'er 2009) and more recently by Fermi-GBM, see e.g. Ryde et al (2010); Iyyani et al (2013Iyyani et al ( , 2015; Larsson et al (2015); Ryde et al (2017); Meng et al (2018Meng et al ( , 2019; Dereli- .…”
Section: Introductionmentioning
confidence: 95%